Effects of temperature on early development of the New Zealand geoduck Panopea zelandica (Quoy & Gaimard, 1835). (6th December 2019) - Sharma, Shaneel S.; Alfaro, Andrea C.; Ragg, Norman L. C.; Zamora, Leonardo N.
Abstract: Ambient seawater temperature is an important factor during the early life stages of marine invertebrates. Temperature is often manipulated in hatcheries to shorten the incubation period before the larval rearing phase. In this study, the effect of temperature on the early development of the geoduck Panopea zelandica was investigated over a 48‐hr period to identify the optimum temperature for fertilization and development in a controlled environment. Eggs and sperm collected from broodstock were exposed to ten temperatures ranging between 11.8 and 23.7°C, and fertilization and subsequent development were monitored over 48 hr. Highest percentages of fertilization were achieved at 23.7°C, which was the highest temperature tested in this study. However, the development of P. zelandica embryos was greatly hindered at temperatures >18.5°C due to a range of abnormalities arising from uneven cell division and cellular blebbing. All larvae died at the highest temperature of 23.7°C within 48 hr of exposure. The combined fertilization success and embryo development data indicate that 18.5°C is the optimal temperature for incubating P. zelandica embryos under hatchery conditions.